Digitalization in Strengthening Good Governance: A Case Study of e-Government Implementation in Local Government - Nur Azizah Manggabarani (Asian Digital Governance Problems, 2024)
Purpose: This study aimed to examine how digitalization contributes to strengthening good governance through the implementation of e-government in Makassar City. It explored how digital systems foster transparency, accountability, citizen participation, and administrative efficiency within a local governance context. Subjects and Methods: This research employed a qualitative case study approach involving government officials, IT officers, administrative staff, civil society representatives, and citizens directly involved in digital public services during 2024. Data were collected through semi-structured interviews, field observations, and document analysis, then analyzed thematically using the principles of qualitative thematic analysis. Results: The findings indicate that digital platforms such as SIPAKATAU, SIPAKALEBBI, and SIPAKARUNG improved public access to information, accelerated administrative services, strengthened procedural accountability, and expanded citizen participation through online complaint systems. The study also identified challenges related to digital literacy, internet accessibility, and institutional adaptation among public employees. Conclusions: Digital governance in Makassar contributed significantly to strengthening good governance, although sustainable implementation requires inclusive access, organizational adaptation, and continuous human resource development.